Regiospecific Formation and Unusual Optical Properties of 2, 5‐Bis (arylethynyl) rhodacyclopentadienes: A New Class of Luminescent Organometallics - Andreas, Steffen; Richard M, Ward; Meng Guan, Tay; Robert M, Edkins; Fabian, Seeler; Magda van, Leeuwen; Lars‐Olof, Pålsson; Andrew, Beeby; Andrei S, Batsanov; Judith AK, Howard; Todd B, Marder (WILEY‐VCH Verlag, 2014)
A series of 2,5-bis(arylethynyl)rhodacyclopentadienes has been prepared by a rare example of regiospecific reductive coupling of 1,4-(p-R-phenyl)-1,3-butadiynes (R[DOUBLE BOND]H, Me, OMe, SMe, NMe2, CF3, CO2Me, CN, NO2, −C[TRIPLE BOND]C-(p-C6H4[BOND]NHex2), −C[TRIPLE BOND]C[BOND](p-C6H4[BOND]CO2Oct)) at [RhX(PMe3)4] (1) (X=−C[TRIPLE BOND]C[BOND]SiMe3 (a), −C[TRIPLE BOND]C-(p-C6H4[BOND]NMe2) (b), −C[TRIPLE BOND]C[BOND]C[TRIPLE BOND]C[BOND](p-C6H4[BOND]NPh2) (c) or [BOND]C[TRIPLE BOND]C[BOND]{p-C6H4-C[TRIPLE BOND]C[BOND](p-C6H4-N(C6H13)2)} (d) or Me (e)), giving the 2,5-bis(arylethynyl) isomer exclusively. The rhodacyclopentadienes bearing a methyl ligand in the equatorial plane (compound 1 e) have been converted into their chloro analogues by reaction with HCl etherate. The rhodacycles thus obtained are stable to air and moisture in the solid state and the acceptor-substituted compounds are even stable to air and moisture in solution. The photophysical properties of the rhodacyclopentadienes are highly unusual in that they exhibit, exclusively, fluorescence between 500–800 nm from the S1 state, with quantum yields of Φ=0.01–0.18 and short lifetimes (τ=0.45–8.20 ns). The triplet state formation (ΦISC=0.57 for 2 a) is exceptionally slow, occurring on the nanosecond timescale. This is unexpected, because the Rh atom should normally facilitate intersystem crossing within femto- to picoseconds, leading to phosphorescence from the T1 state. This work therefore highlights that in some transition-metal complexes, the heavy atom can play a more subtle role in controlling the photophysical behavior than is commonly appreciated.